The Role of Parent-Child Reading in the Development of Children's Early Reading and Writing Abilities: A Multidisciplinary Perspective Review - Yue, Zhang; Hafiz Hanif (Ilmu Inovasi Nusantara, 2025)
Parental education plays a pivotal role in fostering children’s early reading and writing development, yet the mechanisms through which parent–child co-reading supports learning outcomes remain underexplored. This study addresses the problem by investigating how different aspects of co-reading contribute to children’s literacy growth. Specifically, it aims to identify and evaluate the combined influence of three dimensions of co-reading: high-frequency reading sessions, high-quality parent–child interaction, and rich language input. To achieve this goal, we employed a qualitative micro-analysis of recorded and transcribed co-reading sessions from exemplar families. Key variables—reading frequency, interaction quality, and language richness—were measured using observational coding protocols and discourse analysis. Their individual and combined impacts on children’s vocabulary development, comprehension, and cognitive engagement were examined through comparative analysis. Findings show that frequent co-reading sessions significantly enhance children’s vocabulary acquisition and text comprehension. Moreover, high-quality interaction—particularly open-ended questioning and emotional scaffolding—was found to strengthen children’s intrinsic motivation and cognitive flexibility. Language input that included demonstrations of multiple-meaning words and complex sentence structures promoted both receptive and expressive language development. The most impactful results emerged when these three elements functioned synergistically in a dynamic loop of questioning, modeling, and responsive feedback, producing a multiplier effect on learning outcomes. The use of our three-dimensional model as a framework for designing co-reading interventions. Schools, families, and community programs should be equipped with guidelines to implement this model. Future research should expand to longitudinal and multicultural studies, including the integration of smart reading technologies for broader impact